Directed Differentiation: MRI‐Visible siRNA Nanomedicine Directing Neuronal Differentiation of Neural Stem Cells in Stroke (Adv. Funct. Mater. 14/2018). (6th April 2018) - Lu, Liejing; Wang, Yong; Zhang, Fang; Chen, Meiwei; Lin, Bingling; Duan, Xiaohui; Cao, Minghui; Zheng, Chushan; Mao, Jiaji; Shuai, Xintao; Shen, Jun
Abstract : A multifunctional nanoscale polymersome is developed for directing neuronal differentiation of neural stem cells (NSCs) by Jun Shen and co‐workers in article number1706769 . Superparamagnetic iron oxide nanoparticles and small interfering RNA can be co‐delivered into NSCs, allowing for directing neuronal differentiation through silencing the NgR gene and non‐invasive migration monitoring. The study shows the great potential of nanomedicine in stroke treatment using stem cell transplantation.